Encoding Plasticity: The Rise of Molecular Biopolitics and Human Capital. - Lee, Alex Taek-Gwang (University of Toronto Quarterly, 2025)
This article explores the fundamental concept of plasticity in living organisms and its complex relationship with capitalism and its datafication of life. Plasticity is presented as a crucial adaptive mechanism allowing organisms to respond to environmental changes. I examine how capitalism has uniquely developed methods to exploit this biological plasticity for economic growth, transforming adaptive processes into commodifiable resources, and the paradoxical nature of this relationship, where capitalist systems simultaneously depend on, and potentially undermine, the adaptive capacities of living systems. My focus is on how this exploitation ranges from genetic modification of crops to the manipulation of consumer behaviour through neuroplasticity-based marketing strategies. Furthermore, my discussion traces the historical roots of this dynamic, referencing Adam Smith's and Karl Marx's observations on the mechanization of labour and its connection to the division of tasks. It then expands on this by introducing Michel Foucault's concept of disciplinary power and its role in shaping and restricting the plasticity of life within industrialized societies. The article details how this form of power operates through surveillance, normalization, and the meticulous control of bodies, as exemplified by Taylorism in factory settings. My argument goes on to explore the transition from disciplinary power to biopower, a more expansive form of control that regulates life processes on a population scale. It also recounts Foucault's analysis of neoliberalism as a pervasive form of governmentality that shapes human conduct and subjectivity in alignment with market-oriented principles. In conclusion, this work provides an analysis of the connections between biological adaptability, economic systems, and power mechanisms.